Metalanguage : social and ideological perspectives - Coupland, Nikolas, 1950-; Galasiński, Dariusz; Jaworski, Adam, 1957- (Language, power, and social process, 2004)
"The ability of language to refer to itself, or its metalinguistic function, is explored in this volume through the study of explicit comments on speakers' own and other people's talk, reported speech, and stylisation. Metalanguage is theorized as an indispensable aspect of communication and as such an integral part of any sociolinguistic analysis. The book overviews the theory of metalanguage and presents original case studies of metalanguage in lay and professional (including linguists') discourses, the media, parliamentary debates, education, and retail shopping."--Jacket